2010
DOI: 10.1097/jto.0b013e3181f2636e
|View full text |Cite
|
Sign up to set email alerts
|

Follow-Up of Small (4 mm or Less) Incidentally Detected Nodules by Computed Tomography in Oncology Patients: A Retrospective Review

Abstract: In oncologic patients, 28% of small pulmonary nodules detected at initial CT will increase in size, suggesting metastasis. This increase in size tends to occur early, and follow-up CT in 3 months and 6 months would be appropriate in further evaluation. Small nodules that are stable in size for more than 365 days are unlikely to be pulmonary metastasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
19
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 13 publications
4
19
0
Order By: Relevance
“…It is important to note, that the median lesion size of these malignant lesions was smaller compared to all lesions (median lesion size: 6 mm vs. 8 mm). This is in accordance with the literature where many small pulmonary nodules are reported to be benign even in oncologic patients (35). …”
Section: Discussionsupporting
confidence: 93%
“…It is important to note, that the median lesion size of these malignant lesions was smaller compared to all lesions (median lesion size: 6 mm vs. 8 mm). This is in accordance with the literature where many small pulmonary nodules are reported to be benign even in oncologic patients (35). …”
Section: Discussionsupporting
confidence: 93%
“…MacMahon et al reported that the malignancy risk is highly related to its size: 0.2% for nodule < 3 mm, 0.9% for nodules 4–7 mm, and 18% for 8–20 mm [ 25 ]. However, Munden et al found that 28% of small pulmonary nodules detected at baseline CT scan will increase in size, indicating metastatic disease [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Metastatic pulmonary diseases are sometimes detected incidentally during the workup for other diseases . In such cases, almost of them are found by plain radiograph or CT scan .…”
Section: Discussionmentioning
confidence: 99%